The impact of digital marketing in enhancing competitive response: " دراسة ميدانية لآراء عينة من المديرين في عدد من المصارف الأهلية العراقية" - Farhan Talib, ALaa; Mohsen alyasiry, akrem; Dayekh Abd Ali, Nagham (Iraqi Journal for Administrative Sciences, 2024)
The research dealt with the topic of digital marketing in its dimensions (Attract, Engage, Retain, learn, Relate) and its effect on the competitive response in its dimensions (speed, effectiveness, consistency), and the research sought to achieve a set of goals, the most important of which is the extent to which the banks are interested in the concepts of digital marketing and competitive response, and provide An intellectual and philosophical contribution to the variables and dimensions of the research, as the research was conducted in (13) private banks in Iraq were randomly selected, and the research was applied to a sample of (225) people from the administrative leaderships in the researched banks, and the research also adopted the questionnaire as a major tool To obtain data and information, and with a view to data processing, researchers used a set of statistical methods including (Alpha Cronbach test, arithmetic mean, standard deviation, difference coefficient, simple correlation, linear regression, interpretation coefficient, T test, F test), which were applied Through programs (SPSS.19), and one of the most prominent conclusions reached by the research is that digital marketing and competitive response are linked morally and positively, as is marketing figure In a significant way that affects the competitive response, it follows that interest in digital marketing and its proper application in the research banks contributes to improving the competitive response significantly for those banks. In a modern digital technique in order to attract and gain the largest possible number of clients with them, as well as the need to motivate the managers of the research banks in the speed of developing their fields related to their financial, human and technological aspects in order to achieve the goals that they seek.